Low Temperature Selective Catalytic Reduction (SCR) of NOx Emissions by Mn-doped Cu/Al2O3 Catalysts - Deepak Yadav; Ashish R. Kavaiya; Devendra Mohan; Ram Prasad (Bulletin of Chemical Reaction Engineering & Catalysis, 2017)
The 15 mol% Cu/Al2O3 catalysts with different Mn doping (0.5, 1.0, 1.5, mol%) were prepared using PEG-300 surfactant following evaporation-induced self-assembly (EISA) method. Calcination of precursors were performed in flowing air conditions at 500 ºC. The catalysts were characterized by X-ray Diffraction (XRD), X-ray Photoelectron Spectroscopy (XPS), Scanning Electron Microscope Energy Dispersive X-Ray (SEM-EDX), Fourier Transform Infra Red (FTIR), and N2 physisorption. The catalysts activities were evaluated for H2 assisted LPG-SCR of NO in a packed bed tubular flow reactor with 200 mg catalyst under the following conditions: 500 ppm NO, 8 % O2, 1000 ppm LPG, 1 % H2 in Ar with total flow rate of 100 mL/min. Characterization of the catalysts revealed that surface area of 45.6-50.3 m2/g, narrow pore size distribution (1-2 nm), nano-size crystallites, Cu2+ and Mn2+ phases were principal active components. Hydrogen enhanced significantly selective reduction of NO to N2 with LPG over 1.0 mol % Mn-Cu/Al2O3 giving 95.56 % NO reduction at 150 ºC. It was proposed that the synergistic interaction between H2 and LPG substantially widened the NO reduction temperature window and a considerable increase in both activity and selectivity. Negligible loss of catalyst activity was observed for the 50 h of stream on run experiment at 150 ºC. The narrow pore size distribution, thermal stability of the catalyst and optimum Mn doping ensures good dispersion of Cu and Mn over Al2O3 that improved NO reduction in H2-LPG SCR system.